2019
DOI: 10.3390/ijms20030766
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Signalling

Abstract: AMP-activated protein kinase (AMPK) regulates energy homeostasis in eukaryotic cells and organisms [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Phosphorylated AMPK is 100-fold more active than the native protein. Actually, apart from the allosteric regulation, AMPK is involved in a kinase cascade (8,12,17). It has been shown that various growth factors and hormones can promote AMPK activation through its phosphorylation.…”
Section: Amp-activated Protein Kinase (Ampk) Regulation and Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Phosphorylated AMPK is 100-fold more active than the native protein. Actually, apart from the allosteric regulation, AMPK is involved in a kinase cascade (8,12,17). It has been shown that various growth factors and hormones can promote AMPK activation through its phosphorylation.…”
Section: Amp-activated Protein Kinase (Ampk) Regulation and Activitymentioning
confidence: 99%
“…It has been shown that various growth factors and hormones can promote AMPK activation through its phosphorylation. Reportedly, apart from LKB1, calcium/calmodulin-dependent protein kinase (CAMKK), transforming growth factor-beta-activated kinase (TAK1) and ataxia telangiectasia mutated protein may function as AMPK kinases (9,12).…”
Section: Amp-activated Protein Kinase (Ampk) Regulation and Activitymentioning
confidence: 99%
See 3 more Smart Citations